Short-Answer Questions


Short-Answer Questions

Solve: $x^{2}+6 x-\left(a^{2}+2 a-8\right)=0$


$x^{2}+6 x-\left(a^{2}+2 a-8\right)=0$

$\Rightarrow x^{2}+6 x-(a+4)(a-2)=0$

$\Rightarrow x^{2}+[(a+4)-(a-2)] x-(a+4)(a-2)=0$

$\Rightarrow x^{2}+(a+4) x-(a-2) x-(a+4)(a-2)=0$

$\Rightarrow x[x+(a+4)]-(a-2)[x+(a+4)]=0$


$\Rightarrow x+(a+4)=0$ or $x-(a-2)=0$

$\Rightarrow x=-(a+4)$ or $x=(a-2)$

Hence, $-(a+4)$ and $(a-2)$ are the roots of the given equation.


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now